ANALISIS KETIDAKEFEKTIFAN DEKLARASI PANMUNJOM SEBAGAI UPAYA REUNIFIKASI SEMENANJUNG KOREA - Nabila Lam'anah (Journal of International Relations Universitas Diponegoro, 2023)
North and South Korea have made various peace efforts to overcome the issue of denuclearization of the Korean Peninsula. However, so far the peace efforts that have been made by the two Koreas have not been successful. This is caused by the relations between the two countries which are still marked by mutual distrust, lack of cooperation, hatred, and ideological conflict. Then, the two Koreas made peace efforts again called the Panmunjom Declaration in 2018. The main points of this declaration are a commitment to end the confrontation of the legacy of war that has been going on for a long time, to increase cooperative relations between the Koreas, and denuclearize the Korean Peninsula region. At first, the Panmunjom Declaration became a new achievement in the peace of the Korean Peninsula. Over time, the Panmunjom Declaration became ineffective in carrying out its role as a medium for creating peace and denuclearizing the region. This research will answer the question "Why is the Panmunjom Declaration ineffective in improving relations between North Korea and South Korea?". This study aims to analyze the perceptions and misperceptions that occur between the two countries using the theory of perceptions and misperceptions by Robert Jervis. This study used a qualitative research method which explained that what caused the Panmunjom Declaration to be ineffective was due to misperceptions between North Korea and South Korea.